Recent Progress of Wearable Piezoelectric Pressure Sensors Based on Nanofibers, Yarns, and Their Fabrics via Electrospinning. Issue 5 (30th October 2022) - Zhi, Chuanwei; Shi, Shuo; Si, Yifan; Fei, Bin; Huang, Haitao; Hu, Jinlian
Abstract: Highly sensitive flexible pressure sensors are extensively investigated for various applications, such as electronic skin, human physiological monitoring, and artificial intelligence. However, traditional fabrication technologies are hard to realize the large‐area and mass production of wearable sensing devices. Current trend of miniaturization, systematization, and multifunction has raised the problems of total energy consumption, frequent charging, and reduced usage time. These issues have hindered the progress of wearable sensing electronics. In the light of nanomaterial design, mass production, and facile manufacturing, electrospun piezoelectric pressure sensors offer the best properties of self‐powering, breathability, stretchability, and flexibility, providing ideal interfacing platforms for smart wearables. Tremendous advances have been achieved recently in the high sensitivity, piezoelectric output, composite optimization, and nano‐/microstructure design of nonwoven nanofiber membranes. Nevertheless, how to fulfill real textile‐level integration in consideration of biocompatibility, integration, wearability, geometrical design, multifunction, and systematization remains a big challenge. Therefore, recent progress of piezoelectric pressure sensors from electrospun nanofibers to their fabrics is comprehensively summarized. Plentiful strategies, structure designs, and underlying mechanisms that boost the piezoelectric properties are discussed. Lastly, the challenges and possible solutions for the future electrospinning‐based pressure sensing systems are proposed. Abstract : The relationship among nanofibers, yarns, their fabrics, and the electronic textiles, and future research and development trends of wearable piezoelectric pressure sensing systems.